Anterior Trans-odontoid Screw Fixation in Odontoid Fractures - Mohamed Mohamed (Egyptian Spine Association, 2017)
Background Data: Traumatic injury of the axis odontoid process is not uncommon disorder. The options for management include either conservative treatment in the form external stabilization or surgical treatment. Surgical intervention include posterior C1-2 fixation which although of its high fusion rate, it is not a risk free procedure. Anterior trans-odontoid screw fixation gave a comparable fusion rate and at the same time preserves the segment motion. Purpose: to evaluate the safety and efficacy of the anterior trans-odontoid screw fixation in odontoid fractures. Study Design: a retrospective clinical case study. Patients and Methods: The medical records of ten patients who underwent anterior-trans-odontoid screw fixation for type II and shallow type III odontoid fracture were reviewed. The study was conducted in Cairo University Hospitals from January 2012 to May 2015. The Anderson and D’Alonzo classification system for odontoid xc abh35gfes3AWQfractures was used for patient enrollment. All patients were of less than six months duration. Frankel grading system was used for clinical assessment. Results: Ten patients (8 males and 2 females) with a mean age of 37.2 years old were included. Their age ranged from 21 to 55 years. Four cases suffered shallow Type III and six were Type II fractures according to the Anderson and D’Alonzo system. Good outcome results either radiological or clinical were achieved in all patients and all inserted screws were in proper placement. After a mean follow-up of 6 months radiographic fusion was documented in 8 of 9 patients (89%).Conclusion: anterior trans-odontoid screw can be considered a good choice of surgical treatment dens fractures. Excellent fusion rate could be achieved without significant morbidity and early mobilization. (2017ESJ125)